PELAYANAN PEMERINTAH DALAM URUSAN WAKAF PADA KANTOR URUSAN AGAMA (KUA) KECAMATAN SAIL KOTA PEKANBARU TAHUN 2016-2018 - Nugraha, Randy Aulia; ", Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The waqf foundation in Indonesia has been regulated in Article 1 of the Republic of Indonesia Law No.41 of 2004 concerning Endowments, namely: Waqf is a wakif act to separate and / or give up his property to be used forever or for a certain period of time in accordance with his interests for religious purposes and / or general welfare according to sharia. As for the Problem Formulation in this study, namely: First, How is the government service in matters of Waqf at the Office of Religious Affairs (KUA), Pekanbaru City Sail District, 2016-2018. Second, what are the obstacles in government service in matters of Waqf at the Office of Religious Affairs (KUA) in Pekanbaru City Sail City in 2016-2018.               As for the purpose of this thesis, namely: First, To Know the government services in matters of Waqf at the Office of Religious Affairs (KUA), Pekanbaru City Sail District, 2016-2018. Secondly, to find out the inhibiting factors in government service in matters of Waqf at the Office of Religious Affairs (KUA), Pekanbaru City Sail District, 2016-2018. This research is a qualitative research. This research was conducted at the Office of Religious Affairs (KUA) in Sail District. The techniques used to collect data in this study are (1) Interviews, (2) Observations, and (3) Document tracking.               The conclusion of this study shows that the Government Services in matters of Waqf at the Office of Religious Affairs (KUA) in Sail City District of Pekanbaru have not been optimally overall, which is evidenced by the lack of human resources in the service provider, and there is a lack of funds for the implementation team that descends on the field , the writer gives a suggestion that there should be an active role of the government which is represented by the religious affairs office and the parties involved in organizing land waqf to be the initiator who gives deeper attention to the community.  Key Words: Supervision, Responsiveness, Transparency, and Participation.